2016
DOI: 10.1155/2016/6960184
|View full text |Cite
|
Sign up to set email alerts
|

Demographics and Personality Factors Associated with Burnout among Nurses in a Singapore Tertiary Hospital

Abstract: Background. The aim of the study was to evaluate the prevalence and extent of burnout among nurses in Singapore and investigate the influence of demographic factors and personal characteristics on the burnout syndrome. Methods. A cross-sectional survey design was adopted. All registered nurses working in Singapore General Hospital were approached to participate. A questionnaire eliciting data on demographics, burnout (measured using the Maslach Burnout Inventory, MBI), and personality profile (measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
69
1
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 29 publications
17
69
1
12
Order By: Relevance
“…Aunque la literatura muestra una gran heterogeneidad en los resultados encontrados respecto a los factores de riesgo sociodemográficos de burnout, diferentes estudios apoyan que los sujetos más jó-venes presentan niveles mayores de burnout 1,20 . Sin embargo, otros han mostrado resultados opuestos 21,22 e incluso algunas investigaciones han informado de la no existencia de tal relación 23 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aunque la literatura muestra una gran heterogeneidad en los resultados encontrados respecto a los factores de riesgo sociodemográficos de burnout, diferentes estudios apoyan que los sujetos más jó-venes presentan niveles mayores de burnout 1,20 . Sin embargo, otros han mostrado resultados opuestos 21,22 e incluso algunas investigaciones han informado de la no existencia de tal relación 23 .…”
Section: Discussionunclassified
“…Este suele aparecer cuando existe una exposición prolongada a diferentes estresores de tipo emocional e interpersonal, exigiendo una alta implicación emocional con las personas a las que se les provee algún servicio. Aunque originariamente el estudio del síndro-me de burnout se realizó con profesionales que dan servicio a otras personas, en la actualidad se ha hecho extensivo a otro tipo de perfiles laborales 1 . Maslach y Jackson 2 fueron las impulsoras de la teoría clásica del burnout y establecieron la presencia de tres dimensiones que se desarrollan de forma gradual a lo largo del tiempo: el cansancio emocional, entendido como sentimientos de apatía y de no poder dar más de sí mismo en el ámbito emocional y afectivo; la despersonalización, que hace referencia al desarrollo de sentimientos y actitudes de cinismo y de carácter negativo hacia las personas con las que se trabaja; la baja realización personal, entendida como la tendencia a evaluarse negativamente, especialmente en relación a la habilidad para realizar el trabajo y para relacionarse eficazmente en el ámbito laboral.…”
unclassified
“…(20) Similarly, nurses in Singapore have intermediate levels of burnout when compared to their peers from China or the United Kingdom (UK). (21) Singapore likely represents a middle ground, with a confluence of Eastern and Western cultures, and is a unique context to evaluate empathy and burnout. (20) This study was conducted to evaluate empathy and burnout among residents in Singapore.…”
Section: Introductionmentioning
confidence: 99%
“…Queiros et al [36] reported that DP was related to individual age and gender while job rank (senior or junior) and length of working experience were significantly associated with poor sense of PA. In other studies, EE was associated with age and education level [37] and unmarried nurses had high scores of EE and DP and low score of PA. [16] Ang et al [15] also found that age, job rank, and neuroticism were significantly related to EE, DP, and PA.…”
Section: Discussionmentioning
confidence: 95%
“…[14] Moreover, it can be related to nurse shortages in diverse clinical settings. [15][16][17] Burnout has a wide range of symptoms; [17] however, it can be conceptualized into three categories: emotional exhaustion (EE), depersonalization (DP), and reduced personal accomplishment (PA). [18] Emotional exhaustion refers to feelings of being overwhelmed; depersonalization is defined as impersonal feelings that seem unreal or not belonging to oneself; while reduced personal accomplishment means a lack of self-achievement.…”
Section: Literature Reviewmentioning
confidence: 99%